A study on Seed germination of Cassia alata Linn an antiallergenic plant - Thirupathi, M; Kiran Kumar, M; Srinivas, D; Rajendar, K; Jaganmohan Reddy, K (Journal of Phytology, 2012)
Cassia alata known as candle bush or Ringworm tree belongs to Cesalpinaceae family, which was found in diverse habitats in the tropics. C. alata leaves containing some chemical substances like chrysophanic acid, is a common ingredient in soaps, shampoos and lotions. The effectiveness of this plant against skin diseases is confirmed by modern scientific studies. The seed germination was gradually decreased by increasing the age of the seeds. Seed propagation is still used as a specialized tool for breeding purposes and for the propagation of pathogen-free plant material.